2008
DOI: 10.1073/pnas.0809242105
|View full text |Cite
|
Sign up to set email alerts
|

An interferon-related gene signature for DNA damage resistance is a predictive marker for chemotherapy and radiation for breast cancer

Abstract: Individualization of cancer management requires prognostic markers and therapy-predictive markers. Prognostic markers assess risk of disease progression independent of therapy, whereas therapypredictive markers identify patients whose disease is sensitive or resistant to treatment. We show that an experimentally derived IFN-related DNA damage resistance signature (IRDS) is associated with resistance to chemotherapy and/or radiation across different cancer cell lines. The IRDS genes STAT1, ISG15, and IFIT1 all … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

27
530
2
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 511 publications
(576 citation statements)
references
References 17 publications
27
530
2
2
Order By: Relevance
“…Using the same approaches, we found that activation of a STAT1-dependent pathway mediates resistance to radiation treatment and predicts response to adjuvant chemotherapy and radiation in breast cancer patients (30)(31)(32). Thus, these approaches have allowed the identification of biologically relevant and differentially expressed pathways in experimental models.…”
Section: Discussionmentioning
confidence: 94%
“…Using the same approaches, we found that activation of a STAT1-dependent pathway mediates resistance to radiation treatment and predicts response to adjuvant chemotherapy and radiation in breast cancer patients (30)(31)(32). Thus, these approaches have allowed the identification of biologically relevant and differentially expressed pathways in experimental models.…”
Section: Discussionmentioning
confidence: 94%
“…IFN-related DNA damage resistance signature (+) xenografts were more resistant to doxorubicin chemotherapy compared with IFN-related DNA damage resistance signature (−) tumors (45). Moreover, a signature of IFN-related genes was associated with prediction of resistance across cell lines and primary tumors of different cancer types and was associated with a clinically adverse outcome after radiotherapy and chemotherapy for breast carcinoma (45). This signature of an IFN-induced pathway correlated with resistance to 5-AZA-dC and HDAC inhibitor induced DNA damage in SCLC cells.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have identified a strong correlation between the constitutive expression of ISGs, and radiotherapy and chemotherapy resistance (45). Constitutive high expression of IFN/STAT1-regulated genes protected tumor cells from the cytotoxic effect of cisplatin and fludarabine (46,47).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a potential involvement of the ISGylation system in oncogenesis and tumor progression has been documented by the dysregulated expression of ISGylation components in tumors of different histological origin Feng et al, 2008), which could be associated with a poor prognosis of patients (Bektas et al, 2008). In addition, an altered ISG15 regulation is correlated with susceptibility/ resistance to chemotherapeutics and radiation, suggesting that ISG15 can serve as a novel biomarker for drug sensitivity (Desai et al, 2008;Weichselbaum et al, 2008).…”
Section: Introductionmentioning
confidence: 99%